Mindfulness for therapists : understanding mindfulness for professional effectiveness and personal well-being - Zarbock, Gerhard; Lynch, Siobhan, Ph. D.; Ammann, Axel; Ringer, Silka (John Wiley & Sons, 2015)
"Presents the first complete mindfulness program designed to improve the personal and professional well-being and effectiveness of therapists themselves"--Provided by publisher.